PENGARUH MINAT BELI KENDARAAN RODA DUA, PERILAKU PENJUAL, KEPUASAN KONSUMEN TERHADAP KEBUTUHAN MASYARAKAT KOTA ENDE - Damianus Tola; Jou Sewa Adrianus (JURNAL EDUCATION AND DEVELOPMENT, 2024)
This study aims to determine the effect of interest in buying two-wheeled vehicles, seller behavior, customer satisfaction on the needs of the people of Ende city. the type of research used in this research is quantitative descriptive research to explain whether or not the influence of the independent variables of interest in buying two-wheeled vehicles, seller behavior, customer satisfaction on the needs of the people of Ende city. The sampling technique uses random sampling where the sampling technique is based on the data source with the number of vehicle owners more than 1253 two-wheeled vehicles. Data collection techniques using questionnaires for primary data and secondary data using documentation studies. Data processing using SPSS version 17. And data analysis using multiple regression analysis. The results of the study of the dependent variables of interest in buying two-wheeled vehicles, seller behavior, customer satisfaction, contributed 79.8 percent, showing a significant influence on the needs of the Ende Regency city community in buying two-wheeled vehicles. Keywords: Interest, Vehicle, Needs.